2006
DOI: 10.1016/j.ultsonch.2005.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ultrasound on adsorption of Geniposide on polymeric resin

Abstract: The effects of pulse ultrasound with different pulse parameter on the adsorption isotherm and kinetics of Geniposide on Resin 1300 were studied. And the mass transfer model describing the adsorption process was constructed. Amount of Geniposide adsorbed on Resin 1300 in the presence of ultrasound is lower than that in the absence of ultrasound. At our experimental conditions, the adsorption equilibrium constant decreases with increasing ultrasonic intensity and pulse duty ratio, and with decreasing pulse perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 23 publications
3
23
0
Order By: Relevance
“…Enhancements of this nature (i.e., beyond internally controlled deliveries) would only arise from changes in internal properties and could be attributed to sonic shockwaves generating microscopic turbulence within polymer pores. 27 Similar results have been observed for delivery of various drugs from a number of polymers, in which transport increased as a function of agitation to a certain point, after which rates became independent of mixing. 29 However, as also seen in this study sonicated deliveries were faster than those observed under any mixing conditions examined, suggesting that sonic improvements were not solely external.…”
Section: Pah Release Under Non-sonicated Conditionssupporting
confidence: 72%
See 2 more Smart Citations
“…Enhancements of this nature (i.e., beyond internally controlled deliveries) would only arise from changes in internal properties and could be attributed to sonic shockwaves generating microscopic turbulence within polymer pores. 27 Similar results have been observed for delivery of various drugs from a number of polymers, in which transport increased as a function of agitation to a certain point, after which rates became independent of mixing. 29 However, as also seen in this study sonicated deliveries were faster than those observed under any mixing conditions examined, suggesting that sonic improvements were not solely external.…”
Section: Pah Release Under Non-sonicated Conditionssupporting
confidence: 72%
“…[22][23][24][25] The possibility of using ultrasound for improved PAH transport in polymer-liquid systems has been examined by Isaza and Daugulis 16 and results showed significant enhancements in substrate delivery and degradation. Although previous results and conclusions [26][27][28][29] suggest that sonication enhances internal and external delivery, as well as partitioning coefficients, results to date for PAHs 16 cannot be adequately interpreted to identify specific effects in two-phase systems. A mass transport analysis is, therefore, required to provide such insight.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Comparison of the exchange methods shows that the time to reach equilibrium in the traditional method is shorter than that in the ultrasonic one. Ultrasound also enhanced the exchange amount by means of transient cavitation bubbles which are found not only in the fluid phase surrounding the particles but also in the solution within the porous particles, compared to the traditional method [8,9]. The effect of the fold equivalent excess of Li + and Ca 2+ ion exchanges is also clearly seen: the higher the amount of the ions present in the solution, the higher the exchange amount.…”
Section: Resultsmentioning
confidence: 95%
“…They found that phenol desorption rates were enhanced with the ultrasound due to an increase in diffusive transport within the pores. In another study, the effect of ultrasound was investigated on the leaching process [8,9]; Geniposide leaching from the Gardenia fruit. Ultrasound increased the external mass transfer and intraparticle diffusion coefficients.…”
Section: Introductionmentioning
confidence: 99%